Rabbi Leo Baeck living a religious imperative in troubled times - Meyer, Michael A. 1937- (Jewish culture and contexts, 2020)
Rabbi, educator, intellectual, and community leader, Leo Baeck (1873-1956) was one of the most important Jewish figures of prewar Germany. The publication of his 1905 Das Wesen des Judentums (The Essence of Judaism) established him as a major voice for liberal Judaism. He served as a chaplain to the German army during the First World War and in the years following, resisting the call of political Zionism, he expressed his commitment to the belief in a vibrant place for Jews in a new Germany. This hope was dashed with the rise of Nazism, and from 1933 on, and continuing even after his deportation to Theresienstadt, he worked tirelessly in his capacity as a leader of the German Jewish community to offer his coreligionists whatever practical, intellectual, and spiritual support remained possible. While others after the war worked to rebuild German Jewish life from the ashes, a disillusioned Baeck pronounced the effort misguided and spent the rest of his life in England.